Language Learning Styles Preferences Of Kolej Universiti Islam Malaysia (KUIM) English As A Second Language (ESL) Learners - Zarina Ashikin Zakaria; Norhana Abdullah (2024)
This research identifies the learning styles that are preferred by 180 learners of 6 different faculties in Kolej Universiti Islam Malaysia (KUIM). The purpose of this research is to find any difference in learning style preferences of learners in different faculties. The respondents were all Malay young adult learners aged between 20 - 21 years old.